In Vitro Exploration of Endophytes Bacteria from Platycerium Elephantotis Plants as Nitrogen Fixers and Phosphate Solubilizers - Pamungkas, Bayu Aji; Aini, Luqman Qurata; Abadi, Abdul Latief; Trianti, Irisa; Syib`li, Muhammad Akhid; Setiawan, Adi (Research Journal of Life Science, 2023)
Platycerium elephantotis, an African epiphytic fern thriving in Indonesia, is prized for its ornamental value and medicinal potential. It aids in fern succession without harming its host, obtaining nutrients from leaf litter and roots. Special water-storing tissues and CAM photosynthesis enhance its resilience. Endophytic bacteria in its roots likely contribute to nutrient absorption, including phosphate solubilization and nitrogen fixation, similar to other fern species. Studies on these bacteria are crucial for enhancing agricultural practices by reducing chemical inputs and promoting plant growth as plant growth-promoting bacteria (PGPB), particularly in nitrogen fixation and phosphate solubilization. The research was conducted from November 2023 to January 2024. Plant samples were collected from Arjuna Park Conservation Garden, Malang, and endophytic bacteria were isolated using serial dilution and nutrient agar media. Hypersensitivity, phosphate solubilization, and nitrogen fixation tests were conducted to assess bacterial traits. The study obtained six bacterial isolates (PE 5, PE 7, PE 24, PE 25, PE 30, and PE 49) from P. elephantotis with potential as biofertilizers due to their nitrogen-fixing and phosphate-solubilizing abilities. The diverse colony morphologies indicate different bacterial species. All isolates are rod-shaped (bacilli). Gram staining shows that PE 25 and PE 49 are gram-negative, while PE 5, PE 7, PE 24, and PE 30 are gram-positive.